A field study investigating road safety effects of a front brake light. Issue 8 (20th May 2021) - Monzel, Merlin; Keidel, Kristof; Schubert, Wolfgang; Banse, Rainer
Abstract: Recent research shows that braking of vehicles equipped with a front brake light is identified significantly earlier than braking of vehicles without front brake lights. Moreover, the absence of front brake lights leads to more conservative road crossing decisions. These results suggest that front brake lights are able to facilitate the pedestrians' anticipation of dangerous traffic situations, thereby increasing road safety. The present research investigated the effects of front brake lights in the real traffic of the Berlin Tegel Airport airside. A total of 102 vehicles were equipped with front brake lights and circulated in airport traffic for a period of three and a half months. Before and after this test period, 197 staff members were asked about their experiences with and their attitude towards front brake lights. The results show that front brake lights rarely led to misunderstandings, whereas they were significantly more often perceived to facilitate communication avoiding dangerous situations. The attitude towards front brake lights was already positive at the first interview and improved significantly during the measurement period. Overall, a great majority of participants stated that front brake lights improve communication between road users and thus increase road safety.